2002
DOI: 10.1007/s005950200129
|View full text |Cite
|
Sign up to set email alerts
|

Gut Glutamine Metabolism at Different Stages of Sepsis in Rats

Abstract: These results indicate that intestinal glutamine uptake is increased and glutamine utilization is enhanced by glutamine supplementation in early sepsis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2005
2005
2014
2014

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 32 publications
0
6
0
1
Order By: Relevance
“…Compared with alanine (non-metabolized by the gut), intraluminal glutamine was shown to be most protective to the mucosa during IRI [44 ]. In a rat model of sepsis, intestinal glutamine uptake and metabolism seemed to be effective, however, only in the early stages of the insult [45].…”
Section: Macronutrients In Ischaemia and Reperfusion Injurymentioning
confidence: 91%
“…Compared with alanine (non-metabolized by the gut), intraluminal glutamine was shown to be most protective to the mucosa during IRI [44 ]. In a rat model of sepsis, intestinal glutamine uptake and metabolism seemed to be effective, however, only in the early stages of the insult [45].…”
Section: Macronutrients In Ischaemia and Reperfusion Injurymentioning
confidence: 91%
“…We used 40 male Sprague Dawley rats weighing 250-290 g (range: 275±20 g) in this study, and rats were divided into four groups of ten rats each, as indicated hereunder. Induction of severe sepsis was performed in all rats by a cecal ligation and puncture (CLP) model [13,14].…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, the skeletal muscle is the main tissue of Gln synthesis, and the gastrointestinal tract, the kidney, and the immune cells are the consumers of Gln [ 69 ]. Generally, the balance between the uptake and release of Gln is maintained and the plasma Gln level is relatively stable.…”
Section: Glutamine and Argininementioning
confidence: 98%
“…The average level of Gln in plasma is 600-900 μmol/L, which accounts for approximately 60 % of the total body free amino acids pool. The fl uctuation of the plasma level of Gln directly affects the total body amino acid level [ 69 ]. The intracellular concentration of Gln is 30-fold higher than that in plasma.…”
Section: Abnormal Metabolism Of Gln In Burns Patientsmentioning
confidence: 99%